Analisis scientific reasoning siswa pada pokok bahasan optik - Lestari, Aryanti; Utari, Setiya; Imansyah, Harun (WaPFi (Wahana Pendidikan Fisika), 2013)
Scientific Reasoning (SR)  is an important ability for improving students intellectual which consist of ability of explaining, hypotesis, prediction, problem solving, design experiment, control variable, analyze data and determining empiris law to find knowledge by student’s self. Based on previous research found that SR did not measured good enough, it could be seen by document analyzes about the quality of test that is developed at school. Therefore, this research purposed  to develope SR’s test on the subject of optics. SR test were adopted by LCTSR standard. From 45 item which is tested, the were 24 item selected and had reliability 0,68 with high category and the rank of validty 0,5 val 1 with rang category enough to high. By using quantitatif-descriptif method, this reserach was applied by sample 34 students. The result of this test was compared with LCTSR satndard test which has reliability 0,76. It means that LCTSR test which is developed could be used to measure SR.